Characterization and constructive utilization of sludge produced in clari-flocculation unit of water treatment plant. (14th March 2018) - Ahmad, Tarique; Ahmad, Kafeel; Alam, Mehtab
Abstract: All water treatment plants produce waste/residue amid the treatment of raw water. This study selectively investigates the clariflocculator sludge for its physicochemical characteristics and potential reuse options. Sieve analysis, XRF, SEM, XRD, FTIR, and TG-DTA instrumental techniques have been used to characterize the sludge sample. Results show that clariflocculator sludge contains about 78% fine sand having grain size range 150–75 μm. SiO2, Al2 O3, Fe2 O3 and CaO constitute the maximum percentage of chemical compounds present in the sludge and quartz is the main crystalline phase of the sludge. Recycling and reuse of this sludge, especially, as fine sand in preparing mortar, concrete mix and other civil engineering products would pave the way for constructive utilization with safe and sustainable sludge management strategies.